Consumer personality, privacy concerns and usage of location-based services (LBS) - Soo, Shen Hin; Tan, Madeline Tanamal Ka Yen; Ho, Ju Yi; Low, Wen Ling; Maryam Muhammad Yahya,; Ho, Jessica Sze Yin * (Journal of Economics, Business and Management, 2015)
This paper examines the effects of the Big Five personality traits on concern for information privacy (CFIP) and the effects of the formulated concern for information privacy towards perceived risk, which in turn determine location-based services (LBS) usage intention. Data for this research was collected from 291 users and non-users of LBS. Result from Pearson correlation analysis indicated significant relationships exist between: (1) extraversion, and openness with collection; (2) extraversion, conscientiousness, and openness with improper access; (3) extraversion, conscientiousness, and openness with errors; (4) agreeableness, neuroticism, and openness with secondary use. All four dimensions of CFIP are found to have a significant direct relationship with perceived risk of using LBS. Implications for research and practice for location-based service providers are discussed.